Potential Factors Affecting Students’ Participation in English Speaking Classroom across Gender - Atma, Nurul; Muhammad, Anugrah Puspita Ayu; Silawati, Aminah Maulidah Nugraha (Pascasarjana Universitas Negeri Makassar, 2025)
Students’ participation is often regarded as one of the indicators of successful teaching and learning process. Unfortunately, having the students to participate in classroom activities is a challenging task for many foreign language teachers. In relation to the issue, this survey study endeavors to shed a light on the potential factors affecting students’ participation in English speaking classroom. Besides, it takes into account gender differences. There were 32 students, consisting of 16 male and 16 female, participating in this study by filling out 39 items questionnaire. After analyzing the data, it was found that the students were reluctant to participate in English speaking classroom because of lack of preparation, unsure with the correctness of their utterance, insufficient time to process the questions, big class size, underestimating their ability and depending on their classmates. Finally, there was statistically significant difference between male and female students in the way they perceive the factors related to speaking in front of the class and making mistake.